Pengaruh sikap dan kepribadian terhadap kinerja pegawai dengan dimediasi Organizational citizenship behavior pada Unit usaha Rijan Mart Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Hifi Rini Puspita (FADZAT: Jurnal Ekonomi Syariah, 2022)
The aims of this study are: 1) Analyzing attitudes towards organizational citizenship behavior. 2) Analyzing the influence of personality on organizational citizenship behavior. 3) Analyzing the influence of attitudes on employee performance. 4) Analyzing the influence of personality on employee performance. 5) Analyzing the effect of employee performance on organizational citizenship behavior. 6) Analyzing the influence of attitudes indirectly on employee performance through organizational citizenship behavior. 7) Analyzing the influence of personality indirectly on employee performance through organizational citizenship behavior. The population in this study were all 38 employees of the Rijan Mart Islamic Boarding School Riyadlul Jannah Pacet business unit, Mojokerto. The sampling method used the census technique, the data analysis used the help of SPSS version 20 to test the validity with factor analysis, and test reliability with Cronbach. Classical assumption test and multiple linear regression analysis, to verify and prove the research hypothesis. From the results of the study, it can be concluded as follows: 1) 1. Attitude has no effect on organizational citizenship behavior 2) Personality has no effect on organizational citizenship behavior 3) Attitude has a significant effect on employee performance 4) Personality has a significant effect on employee performance 5) Organizational citizenship behavior has an effect significant effect on employee performance 6) Attitude has an indirect effect on employee performance through organizational citizenship behavior 7) Personality has an indirect effect on employee performance through organizational citizenship behavior